Personalised health management systems : the integration of innovative sensing, textile, information, and communication technologies - Nugent, Chris D. (Studies in health technology and informatics, 2005)
Shows a synergy between research efforts in three areas: sensor technologies, advanced textiles and nanotechnology and computing. This book brings together researchers from academia, industry and clinical healthcare provision and focuses the need for multi-disciplinary collaborations in the developments of personalised health management systems.